Comments on 'The Value of the SEC's Accounting Disclosure Requirements'. - Backer, Morton (The Accounting Review, 1969)
Abstract Reliance on statistical and mathematical techniques in accounting research has become more common in recent years. This is a promising development since it expands areas of investigation and links accounting more closely with research activities in related disciplines. In this regard, professor George Benston and others have made some noteworthy contributions. Yet mathematical research sometimes creates an aura of exactitude which may induce reader acceptance of generalizations based on collateral and fragmentary evidence, questionable research methods, or imperfectly conceived conceptual models. Despite this reviewer's respect for Professor Benston's technical competence, it is with the possible existence of such deficiencies that he is primarily concerned. Professor Benston is to be respected for embarking on so ambitious a project. However, for reasons indicated, this writer cannot accept the conclusions reached regarding the effectiveness of the SEC's disclosure requirements. While there may be some substance to the hypothesis, the evidence furnished does not support the findings.